2006
DOI: 10.1111/j.1473-6861.2006.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐generating the ‘self’ in learning: developing a culture of supportive learning in practice

Abstract: This article presents the findings of a project that focused on developing a culture of learning where practitioners were able to engage in supported work‐based learning in a Special Care Nursery (SCN). The project was part of a larger study focusing on the implementation and evaluation of an emancipatory practice development programme in an SCN. The aim of this phase of the study was to gain an in‐depth understanding of how the implementation of practice‐development strategies could enable the creation of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Therefore, if work-based learning or commitment to constant development is not confirmed or controlled in any way, the appreciation of and motivation for learning is easily weakened. Independent studying is seen challenging, because nurses are more used to being passive receivers of information rather than being active seekers of knowledge (Wilson et al, 2006) and therefore they need support and challenging. Learning and studying also means different things to different individuals.…”
Section: Culture Of Work Communitymentioning
confidence: 99%
“…Therefore, if work-based learning or commitment to constant development is not confirmed or controlled in any way, the appreciation of and motivation for learning is easily weakened. Independent studying is seen challenging, because nurses are more used to being passive receivers of information rather than being active seekers of knowledge (Wilson et al, 2006) and therefore they need support and challenging. Learning and studying also means different things to different individuals.…”
Section: Culture Of Work Communitymentioning
confidence: 99%
“…Another illustration comes from the rehabilitation ward in which work was interdisciplinary; there, the documentation system helped one nurse obtain the necessary information from all professionals involved in a patient's care. These reports stress that the complexity of work affected learning in nursing practise (Eraut 2007;Hunter et al 2008) and motivated individual learning (Wilson et al 2006). In addition, this study shows how engagement in work activities led to the discovery of the need for further learning (Billett 2004b(Billett , 2008.…”
Section: Nurses Work As a Learning Environmentmentioning
confidence: 99%
“…For example, environmental influences are foregrounded in research that has shown that nurses require learning time to provide the best patient care (Hunter et al 2008). Previous research has also suggested that, when coupled with supportive relationships, an increased level of work-related challenges influences the confidence of nurses and their motivation to learn Wilson et al 2006). In addition, social interactions, time, and support from peers influence the extent to which nurses utilise research (Gerrish et al 2008;Meijers et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Clarke & Wilcockson, 2001;Fenwick et al, 2012;Wilson, McCormack, & Ives, 2006). Professionals are not simply expected to perform prescribed activities in canonical ways, but rather to adjust their approach to the specific situational reality reflecting both contextual and client-related elements.…”
Section: Professional Education and Developmentmentioning
confidence: 99%